The metaverse in supply chain knowledge sharing and resilience contexts: An empirical investigation of factors affecting adoption and acceptance - Ping-Kuo Chen; Yong Ye; Xiang Huang (Journal of Innovation & Knowledge (JIK), 2023)
This study develops a conceptual framework based on the unified theory of acceptance and use of technology, the network theory perspective, and metaverse characteristics. Data were gathered through questionnaires from 209 Chinese manufacturers, and covariance-based structural equation modelling was the main approach used. The results indicate that performance expectancy, facilitating conditions, and establishing initial trust amongst supply chain partners can drive behavioural intention with respect to metaverse adoption for knowledge sharing to improve supply chain resilience. In addition, sensory feedback is an important characteristic of the metaverse and has a critical influence on adoption behaviour. Moreover, it has a complementary partial mediation effect on the relationship between establishing initial trust amongst supply chain partners and behavioural intention as well as a full mediating effect on the relationship between the initial trust of supply chain partners and behavioural expectations. Finally, sensory feedback moderates the relationship between behavioural intention and expectancy. Our findings contribute to the literature on metaverse adoption in the context of supply chain resilience.
Keywords: M11; 650; Metaverse; UTAUT; Network theory; Supply chain; Resilience; Sensory feedback; Knowledge sharing